The Architectural Influences on Alor Setar Historical Buildings in Kedah, Malaysia - Shukri, Sharyzee Mohmad; Achar, Omar; Naseem, Naajid (MAJ - Malaysia Architectural Journal, 2019)
The area of north-western part of Peninsular Malaysia has had many conflicts through the past centuries, specifically Alor Setar the state capital of Kedah, Malaysia. which affected the identity of the Malaysian Royal town classical form of architecture by the colonial influences, by analyzing the form of the layout and the frontal facade for Istana Pelamin, Balai Besar and Masjid Zahir, as well as illustrating the setting of Medan Bandar, Padang court and Nobat tower’ and defining the ’generic’ or ’classical’ and the ’variant’ or ’ colonial influences’, will understand the basic form of Malaysian classical form of architecture and identify the hybrid elements that has evolved. By studying the elevation characters and the settings of ’Medan Bandar’ or ’Medan Alor Setar’ and highlights the underlying themes of the Malay classical form.